Effect of Hemp Fibre Surface Treatment on the Fibre-Matrix Interface and the Influence of Cellulose, Hemicellulose, and Lignin Contents on Composite Strength Properties - Mohammad Mazedul Kabir; Mohammad Yousef Alhaik; Saud Hamad Aldajah; Kin Tak Lau; Hao Wang; Md Mainul Islam (Advances in Materials Science and Engineering)
Natural fibres have recently become an attractive alternative to synthetic fibres in the implementation of polymer composite structures. Inherent flaws within natural fibres in terms of their constituent contents (hemicellulose, cellulose, and lignin) reduce the compatibility of these fibres with polymer matrices. In this study, the effects of chemical treatments on hemp fibres and the resulted polyester matrix composite are investigated. The fibres were treated with alkali (0–10% NaOH), acetyl, and silane chemicals. Long unidirectional fibre composites were prepared by vacuum-assisted resin transfer moulding (VARTM) process. Thermal properties of the fibres were tested using differential scanning calorimetry (DSC) analyses. The mechanical properties of the composite samples were tested using compression and bending tests. Failure analysis of tested composites was undertaken through Optical Microscope (OM) and Scanning Electron Microscope (SEM). The results showed that the treatments of the 4% NaOH reduced interfacial bonding strength and decreased composite properties compared to untreated samples. At higher concentrations (6–10% NaOH), the mechanical properties of the composites increased as a result of greater interfacial bonding. Different trends were observed in the case of alkalised fibres that were further treated with acetyl and silane treatments. It was observed that the treated fibres effectively improved the bonding properties of composites and was in agreement with the micrographs.